Review of AdS/CFT Integrability: An Overview - Beisert, N; Ahn, C; Alday, L; Bajnok, Z; Drummond, J; Freyhult, L; Gromov, N; Janik, R; Kazakov, V; Klose, T; Korchemsky, G; Kristjansen, C; et al. (2012)
This is the introductory chapter of a review collection on integrability in the context of the AdS/CFT correspondence. In the collection, we present an overview of the achievements and the status of this subject as of the year 2010. © 2011 Springer.